FARC leadership accused of war crimes over child soldiers - Liévano, Andrés Bermúdez (JusticeInfo.net, 2024)
In Colombia, six former FARC leaders have been charged with participating in the recruitment of child soldiers. Following the announcement by the Special Jurisdiction for Peace (JEP), they indicated that they accepted the charges against them.